Value of antiquity in the restoration process of the art nouveau Villa Duelfer in Barlinek = Wartość dawności w procesie renowacji secesyjnej Willi Architekta w Barlinku - Rutyna, Halina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The value assigned to time-worn objects and buildings seems crucial to a conservator?s theoretical beliefs. The notion of antiquity is almost imprinted in the structure of the building itself, as well as in the concept of the time that has lapsed since the erection of the building.
Keywords: zabytki architektury; wartościowanie; renowacja; secesja; architectural monuments; evaluation; restoration; Art Nouveau